ASSESSMENT OF THE POTENTIAL FOR DEVELOPMENT OF AGRITOURISM IN BINH DINH PROVINCE, VIETNAM - Thi Hoai Huong Hoang; Quyet Thang Dao; Thi Thu Thuy Nguyen; Thi Thanh Nhan Tran; Thi Thuy Dung Nguyen; Thi Thuy Giang Nguyen (Tạp chí Khoa học Đại học Đà Lạt, 2023)
This study evaluates the potential for agritourism development in Binh Dinh Province, Central Vietnam. The analytical hierarchical process is used to determine the weights of four factors with 25 measurement criteria to assess agritourism potential. The research results show that Binh Dinh Province has great agritourism potential based on four evaluation factors, including (1) local agricultural tourism resources, (2) the trend for agritourism development and the agritourism market, (3) the local community’s willingness, and (4) the supporting activities of the local government. In particular, the local agricultural tourism resources factor received the highest score, followed by the local community’s willingness and the supporting activities of the local government. The trend for agritourism development and the agritourism market was rated the lowest. Therefore, Binh Dinh has viable opportunities to encourage the growth of agritourism to improve farmers’ livelihoods